Purification and identification of some characters of the fibrinolytic enzyme isolated from the earthwom Perionyx excavatus - Bich Thuy, Le Thi; Tuyen, Do Thi; Ngoc Dao, Nguyen Thi (Academia Journal of Biology, 2014)
A strong fibrinolytic enzyme was isolated and purified from an earthworm of Vietnam: Perionyx excavatus. The purification procedure was described as follows: the earthworms were washed to remove the attached mud and then were left to evacuate the casts from their alimentary tract in distilled water. The living earthworms were homogenized in 0.9% NaCl. The homogenate was centrifuged at 20.000 rmp/min for one hour. The obtained supernatant was precipitated with a 35% and then 60% saturation of ammonium sulfate. The resultant precipitate was dissolved in the 0.02 M sodium phosphate buffer, pH 6 and subjected on the sephacryl S200 gel filtration column. The strongest fibrinolytic fraction was further fractionated by the column chromatography on DEAE cellulose and then on the superdex G75 gel filtration column. The particular activities of two obtained enzymes were 271 and 126 IU/mg and theirs molecular weights were 34 and 28 kDa, respectively. The obtained enzymes were heat-stable and had broad pH range; the optimum temperature was at range 35oC – 45oC and the optimum pH was at range 7-7.5.